MEDIA OF LANGUAGE SHIFT IN BAJAU SAMA KOTA BELUD : SPEAKING, UNDERSTANDING, READING, AND WRITING READING, AND WRITING - Berawati, RENDDAN; Zuraini, Seruji; Adi Yasran, ABDUL AZIZ; Noor Aina, DANI; Nalmon, GOYI (Faculty of Educatipn, Language and Communication, UNIMAS, 2023)
This study investigated language shift among middle-age, adult, and youth age groups of the Bajau Sama Kota Belud indigenous people. The cross-sectional study involved 243 participants, selected using stratified sampling. The questionnaire was based on language transmission assessment by Brenzinger et al. (2003). Results showed that language shift across different skill areas — speaking, understanding, reading, and writing — showed that the Malay language in everyday life is more dominant than their mother tongue among adults and youths. The language skills and the language daily use scores of Bajau Sama adults and youths are not significantly correlated. The two groups manifest the four variables of language shift in Bajau Sama. This study shows that the language shift phenomenon in Bajau Sama is accelerated in the younger generation, and they serve as the living agent of language shift. Following this, there is an urgency to develop a Bajau Sama language corpus and to implement revitalisation initiatives in Kota Belud, Sabah.